Representations of the World Tree in traditional culture of Don Cossacks - Karpun, Mariia (Przegląd Wschodnioeuropejski, 2018)
The subject of this research is the image of a World Tree, its realizations and significances. Tree, as a representation of the axis of the world, so-called axis mundi has been conceptualized since ancient times. The image of a World Tree is relevant to many cultures, as well as the traditional culture of Don Cossacks, in which it is connected to with space zoning (structuring of the world). For example, the underworld (the so-called “тот свет”) is marked by trees, which are growing with their roots up. Moreover, time-characteristics are relate to the image of a World Tree too (marking of time, the point of a new life cycle). This investigation is based on data from dictionaries of Don dialect and materials from the interview with Don Cossacks’s, made by the author. Don traditional culture is in the tideway of an East-Slavonic tradition, but it has have some peculiarities, concerned with regional representations of an image (for instance, ковыла ‘feather grass’ as an embodiment of a World Tree in Don texts of charms).